2016
DOI: 10.21548/31-1-1392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rootstocks on Growth Yield and Fruit Composition of Thompson Seedless Grapes Grown in the Pune Region of India

Abstract: The use of rootstocks is gaining importance in Indian viticulture due to problems associated with abiotic stresses, such as drought and salinity, and also to improve scion characteristics. Thompson Seedless is the only commercial cultivar grown for both fresh consumption and raisin making. Dog Ridge was the only popular rootstock used by grape growers prior to late 1990s. But this rootstock was known to induce more vigour in scions, resulting in reduced bud fruitfulness and thereby fruit yield. To identify alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
47
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 22 publications
(19 reference statements)
14
47
2
1
Order By: Relevance
“…Somkuwar et al (2006) reported higher stock to scion ratio in the case of Flame Seedless grafted on 110-R rootstock. However, Satisha and Prakash (2006) and Satisha et al (2010) reported no adverse effect of stock to scion ratio on the yield of Thompson Seedless grapes grafted on different rootstocks in the initial years of vineyard establishment and also during the long-term evaluations. Errea (1998) suggested biochemical causes rather than anatomical ones responsible for stock-scion incompatibility.…”
Section: Growth Parametersmentioning
confidence: 95%
“…Somkuwar et al (2006) reported higher stock to scion ratio in the case of Flame Seedless grafted on 110-R rootstock. However, Satisha and Prakash (2006) and Satisha et al (2010) reported no adverse effect of stock to scion ratio on the yield of Thompson Seedless grapes grafted on different rootstocks in the initial years of vineyard establishment and also during the long-term evaluations. Errea (1998) suggested biochemical causes rather than anatomical ones responsible for stock-scion incompatibility.…”
Section: Growth Parametersmentioning
confidence: 95%
“…Pruning weight measurements were more efficient to detect differences between rootstocks than leaf area because it is a seasonally integrated measurement of vine vigor, and the pruning is carried on shoots developed during all growing season (Smart and Robinson, 1991). Under traditional vineyard management, 'Rup' is classified as a high vigor rootstock according to the literature (Satisha et al, 2010). In Brazilian viticulture, 'IAC 766' is a high vigorous rootstock developed for table grapes production.…”
Section: Rootstock Effects On Vegetative and Reproductive Vigormentioning
confidence: 99%
“…In addition, rootstocks may promote enhanced adaptability to abiotic stresses such as high or low soil pH (Bavaresco et al, 1992), wet or poorly drained soils (Striegler et al, 1993), and drought (Pavloušek, 2011). Numerous reports have also proved that rootstocks affect vine growth, yield, fruit quality and wine quality (Reynolds & Wardle, 2001;Satisha et al, 2010;Nilnond et al, 2011). However, whether propagation by chip budding on rootstocks has beneficial effects on resistance to foliar diseases such as downy mildew when compared to own-root propagation (e.g.…”
Section: Introductionmentioning
confidence: 99%